(untitled) (NTU Journal of Agriculture and Veterinary Science, 2025)
The study results showed that the characteristics of the fungal colony Rhizoctonia solani match the known descriptions, as the colony colors range from white to dark brown. Six isolates of Trichoderma were isolated from potato roots, belonging to four species: T. hamatum, T. atroviride , T. harzianum, and T. longibrachiatum, and molecular identification was confirmed using ITS1 and ITS4 sequences. Different species of Trichoderma showed strong antimicrobial activity against the growth of the mycelium of R. solani , as the antimicrobial percentage ranged between 81.7% and 96.2%, and the strains T. harzianum BN3 and T. atroviride BN2 recorded the highest antimicrobial percentages. Trichoderma culture filtrate also showed the ability to inhibit the radial growth of R. solani by percentages ranging between 53.7% and 67.4%. The study also showed that T. harzianum BN3 strain was superior in colony growth on different media, its ability to lower pH, and its ability to produce a greater number of spores compared to other species. T. harzianum BN3 strain had the highest biomass and largest colony area on different media (PDA, Czapek-Dox Agar, YEA) and at different temperatures (25, 15, 10 °C), which highlights its high effectiveness in different environmental conditions.